A method for lunar dust-proof functionalization treatment of low-ratio inorganic thermal control coating surface based on simple solution reaction

CN122833696APending Publication Date: 2026-09-29SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510379094.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

然而,现在航天器应用的氧化锌基无机热控涂层普遍存在容易被月尘黏附污染、不易去除等问题,从而导致热控性能下降,难以满足在月面保持更长服役工作需求

Benefits of technology

(1)本发明创新性的公开了一种基于简单的溶液反应对低比值无机热控涂层表面进行防月尘功能化处理的方法,基于简单的溶液反应,通过调节反应温度和反应时间,在氧化锌无机热控涂层表面生长覆盖一层氧化锌纳米小球和纳米柱结构,赋予涂层良好的防月尘的能力。本发明提供的表面防月尘功能化方法处理过的ZnO/K2SiO3白漆,在经历模拟月尘污染实验后,通过简单的旋转和吹扫除尘,黏附前后太阳吸收率的变化率在0.03~0.05之间,与未经处理的ZnO/K2SiO3白漆(污染前后太阳吸收率的变化率在0.18~0.20之间)相比,表现出优异的防月尘性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122833696A_ABST
    Figure CN122833696A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of methods for the surface of low ratio inorganic heat control coating is prevented lunar dust functionalization processing based on simple solution reaction.The method comprises the following steps: (1) low ratio inorganic heat control coating is placed in zinc nitrate solution and soaked for a certain time, then put into oven and heated for a certain time, repeat the step multiple times, and zinc oxide seed crystal is grown on the surface of heat control coating;(2) the heat control coating with zinc oxide seed crystal is placed in the mixed solution of zinc nitrate solution and hexamethylene tetramine solution, and reacts at 80-100 DEG C for 1-5h, zinc oxide nanocolumn is grown epitaxially in the position with zinc oxide seed crystal, after reaction, coating is taken out, dried, and low ratio inorganic heat control coating after lunar dust functionalization processing is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of spacecraft thermal control technology and lunar dust protection technology, and relates to a method for functionalizing the surface of thermal control coatings against lunar dust, specifically a method for functionalizing the surface of low-ratio thermal control coatings against lunar dust. Background Technology

[0002] Due to constant impacts from meteorites and intense radiation, the Moon's surface is covered with a layer of irregularly shaped, electrostatically charged, and highly adhesive lunar dust particles, ranging in size from 0.001 to 130 μm. These dust particles are not only highly adhesive and difficult to detach, but also possess a very high solar absorptivity (α). s =0.79), especially for lunar dust with a particle size of less than 50 μm, it can cause great harm to the mechanical structure and surface temperature control system of spacecraft and probes.

[0003] In existing lunar exploration activities, it has been found that lunar dust adhering to the surface of spacecraft can severely impair the thermal control performance of low-ratio inorganic thermal control coatings. For example, during the 2.5 years that the US Prospector-3 spacecraft operated on the moon, the solar absorptivity of its inorganic thermal control coating, contaminated with lunar dust, decreased from α... s =0.14 increased to α s =0.61, the surface thermal control system suffered severe damage, significantly reducing the service life of the spacecraft and probe. In May 2021, my country's first independently developed Mars rover, "Zhurong," successfully landed on Mars. During its exploration of the Martian surface, the harsh dust environment caused significant interference to "Zhurong's" energy system, forcing it to enter hibernation after a period of operation.

[0004] In the lunar environment, with its extremely high diurnal temperature variations, low-absorption, high-emissivity thermal control coatings are crucial for maintaining the normal operating temperature of spacecraft. Low solar absorptivity and high emissivity ensure better heat dissipation performance, guaranteeing the normal operation of spacecraft and probes on the lunar surface. However, currently used zinc oxide-based inorganic thermal control coatings for spacecraft generally suffer from problems such as easy adhesion and contamination by lunar dust, making them difficult to remove. This leads to a decline in thermal control performance, making it difficult to meet the requirements for extended operational life on the lunar surface. Summary of the Invention

[0005] To overcome the aforementioned shortcomings, this invention provides a method for functionalizing the surface of a low-ratio inorganic thermal control coating against moondust based on a simple solution reaction. The method, based on a simple solution reaction, grows and coats a layer of zinc oxide micro-nano columnar structures (especially filling the recessed "pit" structures) on the surface of the low-ratio inorganic thermal control coating (containing a recessed "pit" structure) by adjusting the reaction temperature and reaction time, effectively reducing the adhesion of moondust to the zinc oxide-based inorganic thermal control coating surface. Compared to an untreated ZnO / K2SiO3 white thermal control coating (with a solar absorptivity of 0.15, reaching 0.33 after lunar dust contamination experiments, with a change rate of 0.18 and a surface lunar dust coverage of 15.4%), the ZnO / K2SiO3 white paint treated using the method of this invention produces a coating with a solar absorptivity between 0.14 and 0.17. After undergoing simulated lunar dust contamination experiments, the coating's solar absorptivity ranges from 0.18 to 0.22, with a change rate between 0.03 and 0.05, and a surface lunar dust coverage as low as 7.5%, demonstrating excellent lunar dust resistance. This invention can functionalize low-ratio thermal control coatings applied to the inner and outer surfaces of lunar spacecraft, probes, and lunar surface infrastructure with lunar dust resistance. While ensuring the target area meets the expected temperature control requirements, it reduces the adhesion of lunar dust particles to the coating surface, lowers the cleaning cost of the coating, and extends the service life of spacecraft, probes, and lunar surface infrastructure. It also has broad application prospects in future Mars and asteroid exploration.

[0006] In a first aspect, the present invention provides a method for functionalizing the surface of a low-ratio inorganic thermal control coating against moon dust based on a simple solution reaction, comprising the following steps: (1) Immerse the low ratio inorganic thermal control coating in zinc nitrate solution for a certain period of time, then put it in an oven and heat it for a certain period of time. Repeat this step multiple times to grow zinc oxide seed crystals on the surface of the thermal control coating. (2) The thermal control coating with zinc oxide seed crystals is placed in a mixed solution of zinc nitrate solution and hexamethylenetetramine solution and reacted at 80-100℃ for 1-5 hours. Zinc oxide nanopillars are epitaxially grown at the position where zinc oxide seed crystals are grown. After the reaction is completed, the coating is taken out and dried to obtain a low ratio inorganic thermal control coating after anti-dust functionalization treatment.

[0007] This invention functionalizes a low-ratio inorganic thermal control coating surface against lunar dust in two steps. First, zinc oxide seed crystals are grown on the thermal control coating surface. Then, based on a simple solution reaction, by adjusting the reaction temperature and time, zinc oxide nanopillars are epitaxially grown at the locations where the zinc oxide seed crystals were grown (including the thermal control coating surface and the recessed "pit" structures). The first step, growing zinc oxide seed crystals on the thermal control coating surface, increases the nanoscale roughness of the coating while simultaneously attaching a layer of zinc oxide nanopillars to the coating surface. The second step, growing zinc oxide nanopillars at the locations of the zinc oxide seed crystals, fills the recessed "pit" structures on the coating surface, reducing the number of "pit" structures. After the lunar dust-resistant functionalization treatment, the coating surface is covered with zinc oxide nanospheres and nanopillars, particularly at the recessed "pit" structures. This increases the nanoscale roughness of the coating, reduces adhesion, and reduces the number of "pit" structures, thereby improving the coating's protection against lunar dust.

[0008] Preferably, in step (1), the substrate of the low-ratio inorganic thermal control coating is zinc oxide, aluminum oxide, zirconium oxide or silicon dioxide.

[0009] Preferably, in step (1), the concentration of the zinc nitrate solution is 0.005 to 0.02 mol / L.

[0010] Preferably, in step (1), the coating is immersed in the zinc nitrate solution for 5 to 10 minutes; The heating temperature is 70–80℃, and the heating time is 5–10 minutes; The number of times step (1) is repeated is 1 to 7, preferably 3 to 5.

[0011] Preferably, in step (2), the concentration of zinc nitrate in the mixed solution is 0.01–0.06 mol / L; The concentration ratio of zinc nitrate to hexamethylenetetramine in the mixed solution is (1-4):(1-4), preferably 1:1; The drying temperature is 70–90°C, and the drying time is 12–24 hours.

[0012] Preferably, in step (2), the diameter of the zinc oxide nanopillar is 0.1 to 3 μm.

[0013] Secondly, the present invention provides a low-ratio inorganic thermal control coating after treatment according to the above method. Before and after a simulated lunar dust pollution experiment, the change rate of the solar absorptivity of the low-ratio inorganic thermal control coating is 0.03 to 0.05, and the coverage of lunar dust on the surface is as low as 7.5%.

[0014] Beneficial effects: (1) This invention innovatively discloses a method for functionalizing the surface of a low-ratio inorganic thermal control coating against lunar dust based on a simple solution reaction. Based on this simple solution reaction, by adjusting the reaction temperature and time, a layer of zinc oxide nanospheres and nanopillars is grown and coated on the surface of the zinc oxide inorganic thermal control coating, endowing the coating with excellent lunar dust resistance. The ZnO / K2SiO3 white paint treated with this lunar dust resistance method, after undergoing a simulated lunar dust contamination experiment, showed a change in solar absorptivity of 0.03–0.05 before and after adhesion, achieved through simple rotation and blowing dust removal. Compared with untreated ZnO / K2SiO3 white paint (where the change in solar absorptivity before and after contamination was 0.18–0.20), this method demonstrates superior lunar dust resistance. (2) This invention provides a method for anti-dust functionalization of the surface of low ratio inorganic thermal control coating based on a simple solution reaction, and provides the optimal treatment scheme. It can perform anti-dust functionalization on the surface of various zinc oxide-based low ratio thermal control coatings, and has the characteristics of simple process and wide application range. (3) This invention provides a method for functionalizing the surface of low-ratio inorganic thermal control coatings against lunar dust based on a simple solution reaction. This method can be used to functionalize the low-ratio thermal control coatings on lunar surface radiators and spacecraft surfaces against lunar dust, effectively reducing the adhesion of lunar dust on the coating surface, extending the coating life, and meeting the requirements for high-reliability service. It has wide applications in future lunar surface exploration, manned lunar landing, lunar base construction, Mars exploration, and asteroid exploration. Attached Figure Description

[0015] Figure 1 SEM images of the coating surfaces in Comparative Example 1 and Example 3; where a and d are SEM images of Comparative Example 1 magnified 600x and 5000x, respectively; b and e are SEM images of Example 3 magnified 600x and 5000x, respectively; c and f are SEM images of Example 3 magnified 5000x and 50000x after undergoing lunar dust contamination experiment, respectively. Figure 2 The UV-Vis diffuse reflectance spectra of the thermal control coatings after lunar dust-proof functionalization in Examples 1-4 and the untreated thermal control coating in Comparative Example 1 before and after being contaminated with lunar dust simulants. Figure 3 The solar absorptivity diagrams show the solar absorbance of the thermal control coatings after lunar dust-proofing functionalization in Examples 1-4 and the untreated thermal control coating in Comparative Example 1 before and after lunar dust contamination. Figure 4 The images show the EDS mapping of Al elements in the thermal control coatings after lunar dust-proofing functionalization treatment in Examples 1-4 and the untreated thermal control coating in Comparative Example 1 after being contaminated with lunar dust simulants. Figure 5 The images show the effects of the thermal control coatings in Examples 1-4 after being functionalized to prevent lunar dust and the untreated thermal control coating in Comparative Example 1 after being contaminated with lunar dust simulants. Detailed Implementation

[0016] To further illustrate the invention's content, features, and practical effects, the invention will be described in detail below with reference to embodiments. It should be noted that the modification methods of the invention are not limited to these specific implementation methods. Equivalent substitutions and modifications made by those skilled in the art based on their reading of the invention's content, without departing from the spirit and essence of the invention, are also within the scope of protection claimed by this invention.

[0017] This invention provides a method for functionalizing the surface of a low-ratio inorganic thermal control coating against lunar dust based on a simple solution reaction. This method features simple experimental setup and operating procedures, making it suitable for low-ratio inorganic thermal control coating surfaces. Specifically, firstly, a layer of zinc oxide seed crystals is grown and coated on the surface of the low-ratio inorganic thermal control coating. Then, based on a simple solution reaction, by adjusting the reaction temperature and reaction time, zinc oxide nanopillars of various directions and sizes are grown at the locations where the zinc oxide seed crystals were grown on the thermal control coating surface. This results in the coating surface being covered by zinc oxide nanospheres and nanopillars, particularly noticeable at the "deep pit" structures on the coating surface. This increases the nanoscale roughness of the coating, reducing the adhesion between the coating and lunar dust, and also reduces the number of "deep pit" structures on the coating surface, improving the coating's protective performance against lunar dust. By functionalizing the coating surface against lunar dust using this method, the adhesion of lunar dust to the surface of the low-ratio inorganic thermal control coating is effectively reduced.

[0018] The following is an exemplary description of the preparation method of the anti-dust inorganic thermal control coating provided by the present invention.

[0019] The low-ratio inorganic thermal control coating is first immersed in zinc nitrate solution for a certain period of time, and then placed in an oven for a certain period of time. This step is repeated 0 to 5 times to grow zinc oxide seed crystals on the surface of the thermal control coating.

[0020] In an optional embodiment, the substrate of the low-ratio inorganic thermal control coating is zinc oxide, aluminum oxide, zirconium oxide, or silicon dioxide; for example, the zinc oxide-based low-ratio inorganic thermal control coating is ZnO / silicate (such as ZnO / K2SiO3), ZnO / phosphate, or ZnO / organic resin.

[0021] In an optional embodiment, the concentration of the zinc nitrate solution is 0.005–0.02 mol / L. The coating is immersed in the zinc nitrate solution for 5–10 minutes. The heating temperature is 70–80°C, and the heating time is 5–10 minutes.

[0022] The thermal control coating with zinc oxide seed crystals was placed in a mixed solution of zinc nitrate solution and hexamethylenetetramine solution and reacted at 80-100℃ for 1-5 hours. Zinc oxide nanopillars were epitaxially grown at the positions where zinc oxide seed crystals were grown. After the reaction was completed, the coating was removed and dried to obtain a low-ratio inorganic thermal control coating after anti-dust functionalization treatment.

[0023] In an optional embodiment, the concentration of zinc nitrate in the mixed solution is 0.01–0.06 mol / L. The concentration ratio of zinc nitrate to hexamethylenetetramine in the mixed solution is (1–4):(1–4), preferably 1:1. The drying temperature is 70–90°C, and the drying time is 12–24 h.

[0024] In an optional embodiment, the diameter of the zinc oxide nanopillars is 0.1–3 μm.

[0025] Compared to the untreated ZnO / K2SiO3 low-ratio thermal control coating (with a solar absorptivity of 0.15, which reached 0.33 after lunar dust adhesion experiments, a change rate of 0.18, and a surface lunar dust coverage of 15.4%), the G-ZnO / K2SiO3 series coatings prepared using the ZnO / K2SiO3 white paint treated by the method of this invention exhibit solar absorptivity between 0.14 and 0.17. After undergoing simulated lunar dust contamination experiments, the coating's solar absorptivity ranged from 0.18 to 0.22, a change rate between 0.03 and 0.05, and a surface lunar dust coverage as low as 7.5%, demonstrating excellent lunar dust protection performance. This invention can be applied to the surface of spacecraft components integrating thermal control and lunar dust protection, meeting the requirements for high-reliability service, and has wide applications in future lunar surface exploration, lunar base construction, and manned lunar landing.

[0026] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0027] Example 1 The ZnO / K2SiO3 zinc oxide inorganic thermal control coating was placed in a mixed solution of 100 ml of 0.04 mol / L zinc nitrate solution and 100 ml of 0.04 mol / L hexamethylenetetramine solution, and reacted in a 90℃ oven for 3 h. After the reaction was completed, the coating was removed and dried in an 80℃ oven for 12 h to obtain the zinc oxide inorganic thermal control coating after anti-dust functionalization treatment.

[0028] Example 2 (1) The ZnO / K2SiO3 zinc oxide inorganic thermal control coating was immersed in 100ml of 0.01mol / L zinc nitrate solution for 5min, and then placed in an 80℃ oven for 5min. This process was repeated 5 times to grow zinc oxide seed crystals on the surface of the ZnO / K2SiO3 zinc oxide inorganic thermal control coating. (2) The thermal control coating with zinc oxide seed crystals was placed in a mixed solution of 100 ml of 0.02 mol / L zinc nitrate solution and 100 ml of 0.02 mol / L hexamethylenetetramine solution and reacted in a 90℃ oven for 3 h. After the reaction was completed, the coating was removed and dried in an 80℃ oven for 12 h to obtain the zinc oxide inorganic thermal control coating after anti-dust functionalization treatment.

[0029] Example 3 (1) The ZnO / K2SiO3 zinc oxide inorganic thermal control coating was immersed in 100ml of 0.01mol / L zinc nitrate solution for 5min, and then placed in an 80℃ oven for 5min. This process was repeated 5 times to grow zinc oxide seed crystals on the surface of the ZnO / K2SiO3 zinc oxide inorganic thermal control coating. (2) The thermal control coating with zinc oxide seed crystals was placed in a mixed solution of 100 ml of 0.04 mol / L zinc nitrate solution and 100 ml of 0.04 mol / L hexamethylenetetramine solution and reacted in a 90℃ oven for 1.5 h. After the reaction was completed, the coating was taken out and dried in an 80℃ oven for 12 h to obtain the zinc oxide inorganic thermal control coating after anti-dust functionalization treatment.

[0030] Example 4 (1) The ZnO / K2SiO3 zinc oxide inorganic thermal control coating was immersed in 100ml of 0.02mol / L zinc nitrate solution for 5min, and then placed in an 80℃ oven for 5min. This process was repeated 5 times to grow zinc oxide seed crystals on the surface of the ZnO / K2SiO3 zinc oxide inorganic thermal control coating. (2) The thermal control coating with zinc oxide seed crystals was placed in a mixed solution of 100 ml of 0.04 mol / L zinc nitrate solution and 100 ml of 0.04 mol / L hexamethylenetetramine solution and reacted in a 90℃ oven for 1.5 h. After the reaction was completed, the coating was removed and dried in an 80℃ oven for 12 h. The zinc oxide inorganic thermal control coating was then subjected to anti-dust functionalization treatment.

[0031] Comparative Example 1

[0032] To compare the reduction in lunar dust adhesion caused by the surface anti-moon dust functionalization treatment, a traditional ZnO / K2SiO3 coating is used as a comparison.

[0033] Figure 1 SEM images of the ZnO / K2SiO3 white paint coating surface treated using the method provided in this invention. Comparing a and b, it can be seen that the "deep pit" structure on the coating surface is significantly reduced after functionalization. Comparing d and e, it can be seen that zinc oxide nanopillars preferentially fill the "deep pit" structure on the coating surface, thus reducing the size of the "deep pit" structure. From c and f, it can be seen that the functionalized coating surface is covered by zinc oxide nanospheres and nanopillars, increasing the roughness of the coating structure, reducing the "deep pit" structure on the coating surface, and improving the anti-dust capability.

[0034] Figure 2 The figures show the UV-Vis diffuse reflectance spectra of the thermal control coatings in Examples 1-4 after lunar dust-resistant functionalization and the untreated thermal control coating in Comparative Example 1 before and after lunar dust simulant adhesion. As can be seen from the figures, after lunar dust simulant contamination, the reflectance of the ZnO / K2SiO3 coating decreased significantly in the 250-2500 nm wavelength range. However, the degree of reflectance decrease in the functionalized zinc oxide thermal control coatings of Examples 1-4 in the 250-2500 nm wavelength range was less than that of Comparative Example 1.

[0035] Figure 3 The graphs show the solar absorptivity of the functionalized zinc oxide thermal control coatings in Examples 1-4 and the untreated thermal control coating in Comparative Example 1 before and after lunar dust adsorption. As can be seen from the graphs, the rate of change in solar absorptivity of the functionalized zinc oxide thermal control coatings in Examples 1-4 after lunar dust contamination is smaller than that in Comparative Example 1.

[0036] Figure 4 EDS mapping images of Al elements in the thermal control coatings after lunar dust-resistant functionalization treatment in Examples 1-4 and the untreated thermal control coating in Comparative Example 1 after lunar dust simulant adhesion are shown. Comparing a and ce, it can be seen that the Al element coverage on the surface of the functionalized coatings in Examples 2-4 is lower than that in Comparative Example 1, with the lowest Al element coverage in Examples 2 and 3, at only 7.5% and 8.8%, respectively. In b, the Al element coverage on the surface of Example 1 is not significantly different from that of Comparative Example 1. This may be because Example 1 did not grow zinc oxide seed crystals on the coating surface before growing nanopillars, affecting the subsequent nanopillar growth process. This resulted in incomplete coverage of the larger "deep pit" structures on the coating surface, leaving large gaps for the larger lunar dust simulants to fall into. Therefore, the results obtained from scanning the Al element mapping image in this area are similar to those in Comparative Example 1.

[0037] Figure 5The figures show the effects of the thermal control coatings in Examples 1-4 (treated with lunar dust resistance) and the untreated thermal control coating in Comparative Example 1 after being contaminated with lunar dust simulants. As can be seen from the figures, after the lunar dust simulant contamination test, the surface of Comparative Example 1 turned dark brown, while the surface of Example 1 was light brown with scattered brown spots. Examples 2-4 showed a lighter color change after contamination, demonstrating better lunar dust resistance.

Claims

1. A method for functionalizing the surface of a low-ratio inorganic thermal control coating with anti-dust based on a simple solution reaction, characterized in that, Includes the following steps: (1) Immerse the low ratio inorganic thermal control coating in zinc nitrate solution for a certain period of time, then put it in an oven and heat it for a certain period of time. Repeat this step multiple times to grow zinc oxide seed crystals on the surface of the thermal control coating. (2) The thermal control coating with zinc oxide seed crystals is placed in a mixed solution of zinc nitrate solution and hexamethylenetetramine solution and reacted at 80-100℃ for 1-5 hours. Zinc oxide nanopillars are epitaxially grown at the position where zinc oxide seed crystals are grown. After the reaction is completed, the coating is taken out and dried to obtain a low ratio inorganic thermal control coating after anti-dust functionalization treatment.

2. The method according to claim 1, characterized in that, In step (1), the substrate of the low-ratio inorganic thermal control coating is zinc oxide, aluminum oxide, zirconium oxide or silicon dioxide.

3. The method according to claim 1 or 2, characterized in that, In step (1), the concentration of the zinc nitrate solution is 0.005 to 0.02 mol / L.

4. The method according to any one of claims 1-3, characterized in that, In step (1), the coating is immersed in zinc nitrate solution for 5 to 10 minutes; The heating temperature is 70–80℃, and the heating time is 5–10 minutes; The number of times step (1) is repeated is 1 to 7, preferably 3 to 5.

5. The method according to any one of claims 1-4, characterized in that, In step (2), the concentration of zinc nitrate in the mixed solution is 0.01–0.06 mol / L; The concentration ratio of zinc nitrate to hexamethylenetetramine in the mixed solution is (1-4):(1-4), preferably 1:

1.

6. The method according to any one of claims 1-5, characterized in that, In step (2), the drying temperature is 70-90°C and the time is 12-24 hours.

7. The method according to any one of claims 1-6, characterized in that, In step (2), the diameter of the zinc oxide nanopillars is 0.1 to 3 μm.

8. A low-ratio inorganic thermal control coating treated by the method according to any one of claims 1-7, characterized in that, Before and after the simulated lunar dust pollution experiment, the change rate of solar absorptivity of the low-ratio inorganic thermal control coating was 0.03 to 0.05, and the surface lunar dust coverage was as low as 7.5%.